2021
DOI: 10.1021/acs.energyfuels.1c00657
|View full text |Cite
|
Sign up to set email alerts
|

Oil-Dispersed α-Fe2O3 Nanoparticles as a Catalyst for Improving Heavy Oil Oxidation

Abstract: Oil-dispersed α-Fe2O3 nanocatalysts were prepared by coating α-Fe2O3 nanoparticles with oleic acid (OA). Mössbauer spectroscopy, X-ray diffraction, and field emission scanning electron microscopy were used to characterize α-Fe2O3 and α-Fe2O3@OA. Their impact on the oxidation process of heavy oil was evaluated using a porous medium thermo-effect cell and thermogravimetry–infrared spectroscopy coupled with isoconversional kinetic analysis. Compared with α-Fe2O3, α-Fe2O3@OA more efficiently catalyzed the combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
(110 reference statements)
4
19
0
Order By: Relevance
“…The Mössbauer core serves as probe in a solid state. It can be used to study the dynamic properties; structural, valence, and charge states of the Mössbauer atom; the phase composition; and the atomic, crystalline, magnetic, and electronic features of the structure of the studied substance [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Separation into magnetic and non-magnetic components makes it possible to facilitate the analysis of the chemical and phase state of iron in individual fractions of fly ashes, which is enriched by separation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mössbauer core serves as probe in a solid state. It can be used to study the dynamic properties; structural, valence, and charge states of the Mössbauer atom; the phase composition; and the atomic, crystalline, magnetic, and electronic features of the structure of the studied substance [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Separation into magnetic and non-magnetic components makes it possible to facilitate the analysis of the chemical and phase state of iron in individual fractions of fly ashes, which is enriched by separation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It contained the following. The internal structures of the device were presented in our earlier works in more detail. ,,,, The heating program of the heater was as follows: RT was increased to 50 °C for 2 min and maintained for 10 min, and then, the heater started to work with a heating rate of 10 °C/min until the temperature of 700 °C. During the reactions, the airflow was equal to 0.5 L/min in the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…The results presented that the presence of copper­(II) stearate decreased the oxidation temperature to lower values in both LTO and HTO districts more than nickel­(II) stearate and iron­(II) stearate. In addition, in our previous works, we reported the addition of oil-soluble and oil-dispersed , catalysts into the heavy oil environment. In our latest studies, we showed that the presence of oil-dispersed , catalysts in heavy oil in both liquid and porous medium due to high-distribution of metal oxides as the active form of catalysts in heavy oil the ignition temperature point, oxidation temperature in both LTO and HTO districts, activation energy of oxidation reaction, and the induction time decreased.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mehrabi-Kalajahi et al recently reported in this journal their study on oil-dispersed α-Fe 2 O 3 nanoparticles as a catalyst for improving heavy oil oxidation. While the reported work was carried out certainly with meticulous planning, the analysis and the presentation of the 57 Fe Mössbauer spectroscopic data are erroneous, which constitute the major part of the above study and the conclusions.…”
mentioning
confidence: 99%